In Vitro Flower Production in Some Species of Hyoscyamus (H. pusillus L., H. arachnoideus Pojark, and H. niger L.) (Journal of Sciences, Islamic Republic of Iran)
Various plant organ segments including segments from roots (root tip, and root collar), stems, leaves, and also seeds of several Hyoscyamus species (i.e. H. pusillus, H. arachnoideus, annual and biennial H. niger from two distinct geographical regions) were cultured on MS media with various growth regulator combinations, to assess the ability of flower production. Statistical assessments showed significant differences between various explants cultured on different media. That is, the subculture of the leaves obtained from H. pusills leaf culture on MS medium containing BAP (1.5 mg/L), on MS medium containing IAA (0.2 mg/L) and Kin (1.5 mg/L), led to the highest flower production. In addition, when cultured on MS medium containing 2,4-D (0.32 mg/L), the seeds of annual H. niger showed high flower production.